1431Dietary patterns and diet quality of Portuguese children and adolescents: the UPPER project. (2nd September 2021) - Moraes, Milena; Oliveira, Bruno; Afonso, Cláudia; Santos, Cristina; Torres, Duarte; Lopes, Carla; Miranda, Renata; Rauber, Fernanda; Antoniazzi, Luiza; Levy, Renata; Rodrigues, Sara
Abstract: Background: Based on a classification that considers the nature, extent and purpose of food processing, this study aims to identify dietary patterns (DPs) and their associations with diet quality. Methods: Sample from the 2015-2016 National Food, Nutrition and Physical Activity Survey (n = 1153;3-17y). Dietary intake from 2 non-consecutive 24h-recalls. Foods classified by NOVA system into 42 subgroups from 4 groups: unprocessed/minimally processed (G1), processed culinary ingredients (G2), processed (G3) and ultra-processed (UPF) (G4). Percentage of grams related to total daily grams consumed were considered to identify DPs by latent class analysis. Adjusted linear regressions were performed to test association with nutritional indicators. Results: Subjects followed 3 DPs: "Unhealthy" (51%), "Traditional" (36%), and "Dairy" (13%). Consumption in NOVA groups/subgroups differentiated them: "Unhealthy", high in G4 and low in G1; "Traditional", high in G1, G2 and G3, but also some subgroups from G4; and "Dairy", high in milk, yogurt and milk-based beverages from G1 or G4 and low in most G3 subgroups. Energy from UPF represented 39% in "Unhealthy" and 34-35% in "Traditional" and "Dairy". Compared to "Traditional" DP, "Unhealthy" was higher in free sugars, and lower in fibre, vitamin A, vitamin C, folates, sodium, potassium, magnesium, and iron. "Dairy" had lower total energy, energy density, fats and sodium, and higher carbohydrates, potassium, calcium, phosphorus and magnesium. Conclusions: "Unhealthy" had the worst nutrient profile, although all DPs presented significant consumption of UPF. This should be considered in food-based interventions and school-feeding policies. Key messages: Half of Portuguese <18 years presented an "Unhealthy" DP.